LIFE SKILLS EDUCATION FOR SCHOOL DROP OUTS IN TAMAN SARI, DISTRICT BOGOR REGENCY - Stefani Nawati EKORESTI (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2019)
Taman Sari Sub-District, Bogor Regency has the potential for fertile soil. But these lands have not been tilled properly. Narrow housing conditions, especially for poor people, do not allow residents to plant crops. Causing the lack of consumption of vegetables; which causes residents become easily sick. In addition, there is also a lot of plastic waste, especially bottled drinking water and other things that come from tourists and fishermen who have not been processed. This condition gave rise to the idea to provide life skills training in making vertical gardens, hydroponic plants and waste management. Besides the need for makeup and haircutting skills also needed especially for orphans fostered by Yasayan Usawatun Hasanah. Community Service Activities (PkM) aims to foster community awareness of the cleanliness of the environment and empower citizens to be more creative and entrepreneurial. Therefore, in addition to the types of activities requested by the residents, UPBJJ-UT Bogor will also teach about identifying the economic value of the work done in the form of determining the cost of goods sold / production. This activity was attended by 50 orphans and it ran smoothly and successfully. Now orphans already have life skills that hope can lift their economy.